Factors Affecting Employee Performance of Education Office in Tabanan Regency - Cahya Sudiarta (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
Human resources (HR) is one of the main assets in a company, the better the HR owned by the company , the easier the company's progress is to obtain. Good human resources are not only filled with employees with quality Intelligence Quotient (IQ), but also filled by employees who are able to control conflicts that occur around them, either in the work environment or in the family environment. The more qualified human resources an organization or company has, it is expected that the ability of the company or organization to compete will be better. Good performance is shown by workers, among others, by the education and training they receive. The actors used to improve worker performance include the education stage, training carried out by workers and worker satisfaction. The purpose of this study was to determine the effect both collectively and individually on the level of education, training and employee satisfaction on the performance of the staff of the Education Office of Tabanan Regency, Bali Province. This Study is a descriptive quantitative research, data collection method using questionnaires and multiple linear regression as data analysis, which was performed using SPSS software version 24. The sample used a number of 92 respondents. The results showed that both simultaneously and individually the level of education, training and employee satisfaction had an influence on the work performance of the employees of the Education Office of Tabanan Regency, Bali Province. The results also showed that the training factor gave the largest contribution to performance.